LEGAL REVIEW OF CHILD PROTECTION AGAINST NARCOTICS THREATS - Uci Novita; Clara Titania Endya; Istislam Istislam; Luvika Sari (Sabtida, 2023)
Children are a particularly vulnerable age group to the effects of drug abuse. When they are exposed to and try illicit substances, it can disrupt their physical health, education and social life. Prolonged use can even cause permanent damage to the body. Given their vulnerability, children have special rights guaranteed by legislation, including protection from the dangers of drugs. This paper examines two main issues: first, the impact of drug abuse on children as victims; second, the role of the state in protecting children from this threat. This study aims to understand the level of vulnerability of children to drug abuse and the forms of legal protection that can be provided. The research used is normative research. Repressive approaches such as criminalization are not the main solution. The state needs to prioritize a restorative approach through physical and mental health recovery and social reintegration. The goal is to ensure that children can return to live a healthy, productive life and have a bright future